Bangladesh and Its Strategic Approaches to Managing the Rohingya Refugee Crisis (Social Science Review, 2026)
Existing scholarship on the Rohingya issue predominantly explains causes of their displacement from Myanmar, complexities in sheltered camps in Cox’s Bazar and myths of their repatriation; there is scant attention to how Bangladesh has approached managing such an ever-evolving large-scale humanitarian crisis. Drawing on wider literature and reports from newspapers, think tanks, and rights bodies, this paper argues that, convincingly or unconvincingly, Bangladesh has adopted pragmatic strategies, combining liberal and stringent approaches to deal with the Rohingya crisis. Broadly, it has taken a cooperative approach, engaging international agencies and actors to manage aid- dependent day-to-day humanitarian affairs. Such a partnership approach has also materialised in the disaster reduction and environmental protection sector, albeit with limitations. Over the period, Bangladesh preferred a look east policy to global negotiation for Rohingya repatriation and emphasised repatriation over local integration and resettlement solutions concerning potential further influxes. Nevertheless, despite concerns raised by the international community and rights bodies, it relied on a security-centric nationalistic approach to thwart Rohingya advancements beyond the camp areas; yet it, on a limited scale, embraced a cooperative approach with camp-based NGOs and agencies for gender-based violence prevention. These findings proffer that managing a refugee crisis is a context-driven enterprise, allowing international and local actors to share the humanitarian burdens, which is as crucial as respecting the host nation’s preferences in dealing with refugees.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 59-84